2020
DOI: 10.1111/jfbc.13229
|View full text |Cite
|
Sign up to set email alerts
|

Provenance effect on bioactive phytochemicals and nutritional and health benefits of the desert date Balanites aegyptiaca

Abstract: Balanites aegyptiaca L. is a multipurpose tree distributed in Africa and Middle East. Several parts of B. aegyptiaca have been suggested to have medicinal uses. So far the effect of ecological origin on the nutritional values and biological activities of B. aegyptiaca genotypes is rarely investigated. Further, metabolic profiling and assessment of the functional food value of B. aegyptiaca leaves are far from complete. In this study, biological activities and profiling of primary and secondary metabolites were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 36 publications
2
22
0
1
Order By: Relevance
“…Leaves are a good source of carbohydrates (28.12%) and proteins (15.86%) and contain ash (9.26%) and dietary fiber (30.75%; Table 1) [12]. Leaves also provide minerals (Table 1), fatty acids (Table 2), amino acids (Table 3) and vitamins (Table 3) [12,13]. Leaves contain antinutrients in meager concentrations (Table 4).…”
Section: Nutritional Composition Of Fruits Seeds and Leavesmentioning
confidence: 99%
“…Leaves are a good source of carbohydrates (28.12%) and proteins (15.86%) and contain ash (9.26%) and dietary fiber (30.75%; Table 1) [12]. Leaves also provide minerals (Table 1), fatty acids (Table 2), amino acids (Table 3) and vitamins (Table 3) [12,13]. Leaves contain antinutrients in meager concentrations (Table 4).…”
Section: Nutritional Composition Of Fruits Seeds and Leavesmentioning
confidence: 99%
“…Panwar and Mathur (2019) also reported that 57 accessions of drumsticks from various regions in India contained highly variable routine flavonoids ranging from close to 0 mg kg -1 dry weight (undetectable) to 60 mg kg -1 dry weight. Different flavonoid content due to genotype differences has also been reported in other plants, such as Cyclocarya paliurus (Fang et al 2011), Chinese Dwarf Cherry (Wang et al 2018), Balanites aegyptiaca (Khamis et al 2020), and Cleome gynandra (Somers et al 2020). Apart from Sumatra, there were several accessions with relatively high levels of flavonoids content that have the potential for genetic improvement in the future, namely Kalimantan, Papua, and Sumba.…”
Section: Discussionmentioning
confidence: 85%
“…It was reported that B. aegyptiaca different parts have many bioactive metabolites such as saponins, terpenoids, alkaloids, flavonoids and steroids which have significant roles in the potentiality of B. aegyptiaca as traditional medicine as antimicrobial, antidiabetic, antiviral, antihelminthic, anticancer agent (Al-Thobaiti & Abu Zeid, 2018). In a recent study, the metabolomic profiling of B. aegyptiaca leaves showed high contents of bioactive secondary metabolites which was positively reflected in the antioxidant, antimicrobial and anticancer activity of their extracts (Khamis et al, 2020). Flowers of B. aegyptiaca showed high content flavonoids and phenolics which affect positively the antioxidant activity of flower extracts (Amadou et al, 2019).…”
Section: Phytochemical Analysis Of Balanites Aegyptiaca By Spectrophotometer Combined With Multivariate Data Analysismentioning
confidence: 97%
“…The effect of ecological origin and provenance on the primary and secondary metabolites distribution in leaves of B. aegyptiaca was assessed. Provenance had affected the nutritional values, metabolomic composition and antioxidant activity of the evaluated leaves (Khamis et al, 2020). Oil, protein and some minerals were evaluated in B. aegyptiaca kernel (Elfeel, 2010) showing variation among different trees and different locations in the content of the previously mentioned parameters.…”
Section: Introductionmentioning
confidence: 99%